El mesolítico en Asturias: Delimitación cronológica y espacial - Fano Martínez, M A (Complutum, 1996)
After a brief historic graphic revision of the chronology of the Mesolithic in Asturias, the interval of time during which the last groups of pure hunter-gatherers inhabited the region is delimited. Later, the distribution of the archaeological data all through the region is considered
Keywords: Asturia, Mesolitico, cronologia